Penerapan Asas Diversi dalam Rehabilitasi bagi Anak sebagai Penyalahguna Narkoba yang Berhadapan dengan Hukum - Nina Zainab (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2023)
The problem of narcotics abuse by minors must be anticipated given the rampant circulation of narcotics today and the weak supervision of government officials (law enforcers) and the surrounding family environment. Laws and regulations have explained and mandated that in resolving children's problems the use of criminal law whose application is carried out through the juvenile justice system should be avoided as a form of protection for children considering their young age and the future that is still far away. For this reason, a policy is needed that positions drug addict children as victims, not as perpetrators of criminal crimes by prioritizing the rehabilitation process as a diversion effort.